Proceedings of the Sixth International Workshop on Computing Education Research 2010
DOI: 10.1145/1839594.1839606
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teachers' attitudes towards object oriented modelling and programming in secondary schools

Abstract: In the year 2004, Bavaria (one of the 16 federal states of Germany) started an innovative subject "Informatics" in its highest type of secondary schools (Gymnasiums). It is comprised of a compulsory stage (grades 6-10), which is followed by an eligible course in grades 11 and 12. The curriculum of the course is based on the "objects first" (or better "modelling first") approach. All relevant object-oriented concepts are introduced and used in the context of standard software, before the students write their fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…The results of this study support the relevant literature, particularly concerning problem solving and algorithmic thinking (Fadi & McHugh, 2001, Muller & Haberman, 2008, system-level-perspective (Gal-Ezer & Zeldes, 2000;Ricks & Jackson, 2009), modelling (Mühling, Hubwieser, & Brinda 2010). They can be used for consolidating available curricular drafts for computer science as a teaching subject at school of the type available in many countries or currently in the state of revision, e.g., for England and Wales, Scotland, the USA, Israel, New Zealand, Germany, India, South Korea, Greece.…”
Section: International Journal Of Research Studies In Computingsupporting
confidence: 86%
“…The results of this study support the relevant literature, particularly concerning problem solving and algorithmic thinking (Fadi & McHugh, 2001, Muller & Haberman, 2008, system-level-perspective (Gal-Ezer & Zeldes, 2000;Ricks & Jackson, 2009), modelling (Mühling, Hubwieser, & Brinda 2010). They can be used for consolidating available curricular drafts for computer science as a teaching subject at school of the type available in many countries or currently in the state of revision, e.g., for England and Wales, Scotland, the USA, Israel, New Zealand, Germany, India, South Korea, Greece.…”
Section: International Journal Of Research Studies In Computingsupporting
confidence: 86%
“…We had 448 teachers answer the online questionnaire more or less completely. As reported in Mühling et al [2010], we found four interesting clusters of teachers as far as their attitudes towards our objects-first concept is concerned. According to their specific preferences, we called them "office users" (25%), "fans of the curriculum" (44%), "anti-programmers" (13%), or "traditional computer scientists" (18%).…”
Section: Research and Resultssupporting
confidence: 71%
“…As far as we have evidence about the success of this conception, this is presented in Section 6. Particularly from the teachers we received quite positive reactions, which might be indicated by the fact that our cluster analysis of their attitudes towards the curriculum [Mühling et al 2010] showed that the largest cluster by far (44%) consist of "fans of the curriculum" or by the contentedness and the missing of any suggestions to change the conception according to the survey of the state institute ISB from 2011 [ISB 2012] (see Section 6 for both surveys).…”
Section: -A Cs In the Modern World 3-b Cs Principles 3-c Topics Inmentioning
confidence: 98%
See 1 more Smart Citation
“…As far as the new subject Informatics in the same country is concerned, research has just begun. In the same country a survey among the Informatics teachers [52] was conducted in autumn 2009. About 500 answered the online questionnaire.…”
Section: Dm: 3-educational Relevant Areas\ Socio-cultural Related Facmentioning
confidence: 99%